THE EFFECT OF THE SCRAMBLE METHOD BASED ON QUESTION CARDS ON STUDENTS’ LEARNING OUTCOMES ON THE MATERIAL OF PLANTS AS A SOURCE OF LIFE ON EARTH IN GRADE IV OF INPRES TOUNWAWAN ELEMENTARY SCHOOL - Umarella, Melati I. S; Kempa, Titin; Wattimury, Ince; Septory, Jekriel (Bio-Lectura : Jurnal Pendidikan Biologi, 2025)
This research was initiated because student learning outcomes were not yet optimal in science and science lessons on Plants, the Source of Life on Earth, one of the important materials in science and science subjects in elementary schools. This material contains basic concepts about the role of plants in ecosystems and human life. However, students often have difficulty understanding this material because of the limited interactive learning methods. The question card-based scramble method is proposed as a learning approach to improve student learning outcomes. This method involves using question cards containing queries or information that students need to rearrange according to the correct concept. This research aimed to determine the effect of the question card-based scramble method on the materials of Plants, Sources of Life on Earth, and class IV at SD Inpres Tounwawan. This research uses a pre-experimental quantitative approach with a one-group pretest-posttest design. In this design, one group of subjects is given a pretest to determine the condition before treatment, followed by a posttest to measure changes after the treatment is given. Based on the data that has been collected from the results of data analysis on student test results in the pretest, it is still relatively low because they have not met the minimum completion criteria score, namely 65. Of the total 20 students, only 1 student meets the minimum completeness criteria. Based on the posttest results of class IV students, all of them have passed the minimum completion criteria score and reached 83%. Based on the T-test table above, the sig value can be explained. (2-tailed) 0.000 < 0.05, then there is an influence of the scramble method on learning outcomes for science material.